2001
DOI: 10.1103/physrevstab.4.022001
|View full text |Cite
|
Sign up to set email alerts
|

Solving Maxwell eigenvalue problems for accelerating cavities

Abstract: We investigate algorithms for computing steady state electromagnetic waves in cavities. The Maxwell equations for the strength of the electric field are solved by a mixed method with quadratic finite edge (Nédélec) elements for the field values and corresponding node-based finite elements for the Lagrange multiplier. This approach avoids so-called spurious modes which are introduced if the divergence-free condition for the electric field is not treated properly. To compute a few of the smallest positive eigenv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 26 publications
0
51
0
Order By: Relevance
“…References [1,5,6] and references therein. One such application is the analysis of the electromagnetic cavity resonator.…”
Section: The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…References [1,5,6] and references therein. One such application is the analysis of the electromagnetic cavity resonator.…”
Section: The Problemmentioning
confidence: 99%
“…We assume that a sparse basis C for the null space of A is available, as is the case in several applications; see for instance References [1][2][3] and their references. A relevant feature of the considered setting is that the dimension of the null space is very high, compared with the problem dimension, reaching up to, say, one-third of the entire problem dimension.…”
Section: The Problemmentioning
confidence: 99%
“…This algorithm is well-suited since it does not require the factorization of the matrices A or M . In [2,3,4] we found JDSYM to be the method of choice for this problem.…”
Section: The Eigensolvermentioning
confidence: 99%
“…This is very time consuming even if the conjugate gradient method is applied with a good preconditioner. In most of our experiments the JacobiDavidson algorithm was much more effective than the implicitly restarted Lanczos algorithm as implemented in ARPACK [5] for solving the cavity and other eigenvalue problems [2,3]. In this study we investigate three factorization-free algorithms for solving (13)…”
Section: Solving the Matrix Eigenvalue Problemmentioning
confidence: 99%
“…In earlier studies [2,3] we found that for large eigenvalue problems the JacobiDavidson algorithm [4] was superior to the Lanczos algorithm or the restarted Lanczos algorithm as implemented in ARPACK [5]. While the Jacobi-Davidson algorithm retains the high rate of convergence it only poses small accuracy requirements on the solution of the so-called correction equation, at least in the initial steps of iterations.…”
Section: Introductionmentioning
confidence: 99%